Academic Procrastination: Prevalence and Causes from the Point of View of Undergraduate Students - Abu Ghazal, Muawia (Jordan Journal of Educational Sciences, 2012)
This study aimed at investigating the prevalence of academic procrastination and it's cause from the point of view of the undergraduate students, and whether these differed according to students’ gender, academic level, or specialization. The sample consisted of (751) undergraduate students (222 male, 529 female), from all faculties of Yarmouk University. The results showed that 21.6% of participants exhibitede a high level of procrastination, 60.3% participants exhibited an average level, and 18.1% of them exhibited a low level. Significant differences were found due to academic level; procrastination level among fourth year was higher than all other years, but no significant differences were found due to students’ gender, or specialization. The result also showed that the causes are order in this: fear of failure, instructor style, aversive task, risk taking, resisting discipline control, and classmate pressure. The results also revealed that levels of resisting discipline, risk taking, classmate pressure were higher among male than female students. But the level of fear of failure was higher among female than male students. Finally, significant differences were found in the field of fear of failure, classmate pressure, and instructor style due to different academic levels.